L2 Writing and L1 Composition in English: Towards an alignment of effort - Baker, Beverly (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2008)
AbstractIn North American university contexts, the language diversity found in English mainstream composition (“L1”) classrooms resembles more and more that found in ESL (“L2”) writing classrooms. As these two groups become less differentiated, those specifically trained in L2 writing might well wonder whether the needs of the non-native speakers of English are acknowledged and addressed in the mainstream classrooms. The author examines several different theoretical constructs that have informed and continue to inform the literature on L1 composition pedagogy, demonstrating that some of these allow for the inclusion of linguistically diverse groups better than others. Fortunately, the recent turn to social and critical approaches to teaching composition reflect well the preoccupations of both L1 and L2 writing teachers. More and more attention is being paid to discussions of “linguistic diversity,” a term which now includes non-native speakers. This suggests a future convergence in the activities of instructors of L1 and L2 writing, leading to benefits for linguistically diverse groups.